The influence of organic pollution resulting from the connection of some polluted small rivers to the Shatt al-Arab on the fish assemblage - Abdullah, Abdul Hussein (Iraqi Journal of Aquaculture, 2025)
Due to the lack of studies dealing with the influence of organic pollutants on fish assemblages in the Shatt Al-Arab River, the present study was done to explain the impact of these pollutants on the composition, abundance, and diversity of fish in the river near the points of discharge of these rivers in the Shatt Al-Arab River. The samples were collected monthly from January to December 2024. Some ecological parameters were measured in the study region As water temperature, salinity, hydrogen ion concentration, dissolved oxygen, biological oxygen demand, total nitrate, and total phosphate. Out of the total of 26 fish species that were caught, five were native, eight were exotic, and 13 were marine fish species belonging to 20 genera, 15 families, and nine orders, all of them affiliated with the bony fish Osteichthyes class. Four species recorded the highest values of numerical relative abundance and formed 68.64% of the overall number of species. The present study concluded that the region has high organic pollutants and total nitrate and phosphate concentrations, with a clear impact on the composition, abundance, and diversity of fish assemblages near these rivers, particularly those meeting the Shatt Al-Arab River.